ECOLOGICAL MARKETING AS A TOOL OF STRATEGY OF HOTEL BUSINESS AND TOURISM DEVELOPMENT (Economic journal of Lesya Ukrainka Volyn National University, 2020)
The essence of the concept of ecological marketing is considered. Different approaches and views on the essence of the concept of "environmental marketing" are clarified. The role of ecological marketing for the development of hotel enterprises around the world is proved. The understanding of ecological marketing in relation to the tools of its application is outlined and their differences are established. The definition of ecological marketing of the hotel enterprise is given. An overview of the application of environmental marketing in the largest hotel chains in the world. Problems of ecological marketing and business development are analyzed.
Keywords: ecological marketing, hotel economy, ecological branding, ecobranding, «green» marketing, Hilton, Marriot.